Marangoni driven boundary layer flow past a flat plate in nanofluid with suction/injection - Md. Arifin, Norihan; Mohd Nazar, Roslinda; Pop, Ioan (American Institute of Physics, 2010)
The problem of Marangoni convection boundary layer flow past a flat plate in a nanofluid when the wall is permeable, where there is suction or injection effect, is studied using different types of nanoparticles. The general governing partial differential equations are transformed into a set of two nonlinear ordinary differential equations using unique similarity transformation. Numerical solutions of the similarity equations are obtained using the Runge‐Kutta‐Fehlberg (RKF) method. Three different types of nanoparticles, namely Cu, Al2O3 and TiO2 are considered by using water as a base fluid with Prandtl number Pr = 6.2. The effects of the suction or injection parameter on the flow and heat transfer characteristics are discussed.